Genetic Characterization of the Immortalized Human Nasopharyngeal Carcinoma Cell Line NPC/HK1 - Anna Makowska; Udo Kontny; Josef vanHelden; Barbara Hildebrandt; Herdit M. Schüler; Ralf Weiskirchen (Cancer Medicine)
ABSTRACT Background Human nasopharyngeal carcinoma (NPC) cell lines are in vitro model systems that are widely available, easy to handle, and provide an unlimited supply of material. They also bypass ethical concerns associated with the use of primary human cells or tissue. However, many of these cell lines including 5‐8F, 6‐10B, CNE‐1, CNE‐2, HNE‐1, HONE‐1, SUNE1, SUNE2, and NPC‐TW01 have been shown to be misidentified or cross‐contaminated. While simple molecular genotyping techniques such as short tandem repeat profiling of human cell lines are available to confirm cell line identity, scientists often do not implement strategies to avoid misidentification. This has resulted in a large volume of publications containing incorrect information. Methods In this paper, we have established a cell line karyogram that contains several marker chromosomes and a set of typical aberrations characteristic of NPC/HK1. Results and Conclusions Combined with the typical multiloci short tandem repeat signature of NPC/HK1, the cytogenetic analysis provides an effective means to avoid unreliable experimental outcomes and scientific misinterpretation.